Capturing Natural Product Biosynthetic Pathways from Uncultivated Symbiotic Bacteria of Marine Sponges Through Metagenome Mining: A Mini-Review - Agustinus Robert Uria (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2015)
Symbiotic bacteria associated with marine sponges have frequently been proposed as the true producer of many bioactive natural products with potent anticancer activities. However, the majority of these complex symbiotic bacteria cannot be cultivated under laboratory conditions, hampering efforts to access and develop their potent compounds for therapeutic applications. Metagenome mining is a powerful cultivation-independent tool that can be used to search for new natural product biosynthetic pathways from highly complex bacterial consortia. Some notable examples of natural products, in which their biosynthetic pathways have been cloned by metagenome mining are onnamide A, psymberin, polytheonamides, calyculin, and misakinolide A. Subsequent expression of the pathways in easily culturable bacteria, such as Escherichia coli, could lead to the sustainable production of rare promising natural products. This review discusses principles of metagenome mining developed to gain access to natural product biosynthetic pathways from uncultured symbiotic bacteria of marine sponges. This includes detecting biosynthetic genes in sponge metagenome, creating large metagenomic library, rapid screening of metagenomic library, and clone sequencing. For many natural products made by modular polyketide synthases (PKSs) and hybrids with non-ribosomal peptide synthetases (NRPSs), their biosynthetic pathways as well as structures of final products can be predicted with high accuracy through bioinformatic analysis and sometimes combined with functional proof. Further metagenome sequencing integrated with single-cell analysis and chemical studies could provide insights into the remarkable biosynthetic capacity of uncultivated bacterial symbionts, thereby facilitating the discovery and sustainable production of a wide diversity of sponge-derived complex compounds.